Quality Assurance and Continuous Improvement in Higher Education: A Case Study of Nepal - Bista, Chhatra Bahadur (AMC Multidisciplinary Research Journal, 2025)
This research explores the role of Quality Assurance (QA) in fostering continuous improvement within Higher Education Institutions (HEIs) in Nepal. Amid increasing demands for educational quality, QA is critical for institutional accountability and improvement. The objective of the study was to (1) assess the effectiveness of existing QA processes, (2) identify key challenges hindering QA implementation, and (3) propose actionable recommendations for enhancement. Employing a mixed-methods approach, data were collected through surveys of 400 stakeholders (faculty, students, administrators) and in-depth interviews with 10 key informants. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data underwent thematic analysis. Findings reveal that 75% of respondents perceive QA processes as effective, with faculty showing higher satisfaction (Mean=4.1) compared to students (Mean=3.5). Stakeholder engagement strongly correlates with QA effectiveness (r=0.65, p<0.01). Key challenges include resistance to change and resource constraints. Successful institutions integrate QA into their culture, leverage technology, and prioritize professional development. The study concludes that embedding QA into institutional culture and actively involving stakeholders are crucial for sustainable improvements. Recommendations include incentivizing stakeholder engagement through policy, resource allocation for technology adoption, and promoting a culture of accountability, thereby enhancing the efficiency and effectiveness of QA frameworks in HEIs.